Brief Report: CYP2B6 516G>T Minor Allele Protective of Late Virologic Failure in Efavirenz-Treated HIV-Infected Patients in Botswana. (1st August 2017) - Vujkovic, Marijana; Bellamy, Scarlett L.; Zuppa, Athena F.; Gastonguay, Marc; Moorthy, Ganesh S.; Ratshaa, Bakgaki R.; Han, Xiaoyan; Steenhoff, Andrew P.; Mosepele, Mosepele; Strom, Brian L.; Aplenc, Richard; Bisson, Gregory P.; et al.
Abstract : Background: CYP2B6 polymorphisms that affect efavirenz (EFV) concentrations are common, but the effect of this polymorphism on HIV virologic failure in clinical practice settings has not fully been elucidated. Our objective was to investigate the relationship between the CYP2B6 516G>T genotype and late virologic failure in patients treated with EFV in Gaborone, Botswana. Setting: We performed a case–control study that included 1338 HIV-infected black Batswana on EFV-based antiretroviral therapy (ART). Patients were approached for enrollment during regular visits at one of the outpatient HIV clinics between July 2013 and April 2014. Methods: Cases experienced late HIV failure, defined as plasma HIV RNA >1000 copies/mL after maintaining viral suppression (<400 copies/mL) for at least 6 months. For each case, a total of 4 control patients were randomly sampled from the same population. Controls had plasma HIV RNA <400 copies/mL on ART for at least 6 months. Logistic regression was used to determine the adjusted odds of late HIV failure by 516G>T genotype. Results: After adjustment for the confounding variables age and CD4 count, the CYP2B6 516 T-allele was protective against late HIV virologic breakthrough, adjusted OR 0.70; 95% CI: 0.50 to 0.97. Conclusion: The CYP2B6 516 T-allele was protective against late virologic breakthrough in patients with initial (6 month) HIV RNA suppression on EFV-based ART. Future studies are needed to assess long-term viral benefits of identifying and offering EFV containing ART to black African HIV-infected patients with CYP2B6 T-alleles, especially given the wider availability of a single pill EFV in this setting. Abstract : Supplemental Digital Content is Available in the Text.